Toluene-induced erythrodermic lichen planus - Hamdi, Dooha; Alhamdi, Khalil I (Indian Journal of Case Reports, 2022)
Lichen planus is an inflammatory disease that affects the skin and mucous membrane. The exact etiology is unknown, but it is considered an immunologically mediated disease toward unrecognized antigen possibly located at the basal cell layer. Many clinical variants are recognized. Lichen planus-like lesions can be seen in chronic versus host disease, drugs, and chemicals. Here, we report a new case of a male patient who was exposed to toluene-containing compounds after which he developed an erythrodermic eczematous and lichenoid eruption, which is to the best of our knowledge, the third case of toluene-induced lichen planus reported worldwide and the first case in our country.